1982
DOI: 10.2535/ofaj1936.58.4-6_1231
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Abnormal Origins of the Left External and Internal Carotid Arteries in the Japanese Monkey

Abstract: Summary : We encountered two cases of abnormal origins of branches arising from the arch of the aorta.That is to say, in the first case, the aortic arch gave directly off the left external carotid artery as its second branch and the left internal carotid artery as its third branch.In the second case, the aortic arch gave directly off the left external carotid artery as its second branch and the left brachiocephalic trunk dividing into the left internal carotid and the left subclavian artery as its last branch.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Adachi (1928) and others in man, and Suzuki (1982) and Tanuma et al (1982) in the Japanese monkey have described the lack of the common carotid artery, respectively. However, both the internal and external carotid arteries in these reported cases arose directly from the aortic arch, the brachiocephalic trunk or the left subclavian artery.…”
Section: Discussionmentioning
confidence: 99%
“…Adachi (1928) and others in man, and Suzuki (1982) and Tanuma et al (1982) in the Japanese monkey have described the lack of the common carotid artery, respectively. However, both the internal and external carotid arteries in these reported cases arose directly from the aortic arch, the brachiocephalic trunk or the left subclavian artery.…”
Section: Discussionmentioning
confidence: 99%
“…Aplasia of the Le CCA. It was noted that the separated ECA in the monkey is formed by the sequent ventral aortic root of the cranial part from the fourth PAA on the le side, while the le ICA is formed by the sequent dorsal aortic root of the cranial part from the le fourth PAA; consequently, the le CCA is not formed [32]. Hovewer, it was noted, too, that the absence of the le CCA in a human is a consequence of the persistence of the le DC with an involution of the le third PAA ( Figure 1); the le ICA would thus originate from the le fourth PAA proximal to the origin of the le SA [1].…”
Section: Cca Aplasiamentioning
confidence: 99%
“…Summarizing these data we have recorded 87 published and/or cited cases of the CCA aplasia in the last 233 years (1784-2017). This number was increased by four when we took into account the following cases: Nizankowski et al [94], as cited [32] have only reported the independent aortic origin of the left ECA and ICA as the type XIII without any additional data; Kunishio et al [53,95] reported the same case twice; Kobayashi et al [96] described the bilateral absence of the CCA and ICA, but they did not either mention the status of the ECAs; and Uchino et al [46] labeled the separated right ICA and ECA origin from "the BT" and not from the right CCA, although the right SA had the independent origin from the NAA.…”
Section: Collateral Pathwaysmentioning
confidence: 99%